Current Status of Sezs in India: An Overview of SEZs in India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In fact, India was the first Asian country to recognize the importance and effectiveness of Export Processing Zone (EPZ) and the first EPZ came into being in 1965 in Kandla, Gujarat. It was followed by the Santa Cruz export processing zone which came into operation in 1973.